Theoretical and methodological basis of an integrated approach to optimization of criteria of the life cycle of a construction development project - MALYKHIN, Mykhailo; DUBENSKYI, Oleksandr; KUZMICH, Yaroslav; KRYVDA, Kyrylo (Ways to Improve Construction Efficiency, 2025)
The article is devoted to the study of the theoretical and methodological foundations of an integrated approach to optimization of criteria of the life cycle of a construction development project. In modern conditions of development of the construction market, characterized by high dynamics of changes, growing environmental requirements and the need to increase the efficiency of resource use, the problem of optimization of criteria of the life cycle of development projects is becoming particularly relevant. Traditional methods of management of the life cycle of construction projects often do not take into account the entire spectrum of factors influencing their successful implementation, and also do not provide sufficient flexibility in responding to changes in the external environment. An integrated approach to optimizing life cycle criteria involves comprehensive consideration of economic, environmental, technological and social aspects of project activities. Particular attention is paid to the analysis of modern concepts of development project management, in particular the Life Cycle Costing (LCC), Value Engineering (VE) and Building Information Modeling (BIM) methodologies, which provide comprehensive resource management and effective decision-making at all stages of the life cycle. It is determined that the main criteria for optimizing the life cycle of a construction project are minimizing costs throughout the cycle, increasing environmental sustainability, ensuring the innovation of design solutions and compliance with the developer’s strategic goals. The use of an integrated life cycle assessment model based on a combination of multi-criteria analysis and risk management methods is proposed. Special emphasis is placed on the importance of digitalization of life cycle management processes of development projects. The use of BIM technologies, intelligent data analysis (Big Data), artificial intelligence (AI) and blockchain solutions allows you to automate the processes of planning, implementation and control of projects, which helps to increase their efficiency and reduce risks. The issue of adaptive life cycle management in the context of modern challenges, such as urbanization, climate change and instability of the economic environment, is also considered. An algorithm for integrating modern management tools into the process of planning and implementing construction projects is proposed, which allows you to increase their flexibility and resistance to external changes. The results of the study can be used to improve the management of construction development projects, develop methodological approaches to assessing their effectiveness, as well as to create new models for optimizing the life cycle of projects taking into account modern market requirements and innovative technologies.